2019
DOI: 10.3390/nu11081937
|View full text |Cite
|
Sign up to set email alerts
|

Association between Grain Intake, Nutrient Intake, and Diet Quality of Canadians: Evidence from the Canadian Community Health Survey–Nutrition 2015

Abstract: The new Canada’s Food Guide (CFG) recommends whole grains foods as the primary choice of grain products in the daily diet. This study examined whether higher shares of whole-grain consumption, beyond the recommended levels (i.e., above half) of the daily grain intake, are linked with optimal diet quality and intakes of some key nutrients, for both children and adolescents and adults in Canada. To meet the objective of this study, we used the Canadian Community Health Survey (CCHS)–Nutrition 2015, which is a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…En nuestro estudio se observó que el IMC, PC y la subsecuente obesidad abdominal, se presenta con una alta prevalencia, pero destaca una menor proporción en el grupo que cumple 3 o más recomendaciones alimentarias, respecto a los que cumplen menos o ninguna recomendación. Existe suficiente evidencia nacional e internacional que relaciona una mala calidad de alimentación con malnutrición por exceso 33,34,35 y que, las Guías Alimentarias, se alzan como una herramienta educativa eficaz para mejorar o mantener estilos de vida saludables 36 .…”
Section: Resultsunclassified
“…En nuestro estudio se observó que el IMC, PC y la subsecuente obesidad abdominal, se presenta con una alta prevalencia, pero destaca una menor proporción en el grupo que cumple 3 o más recomendaciones alimentarias, respecto a los que cumplen menos o ninguna recomendación. Existe suficiente evidencia nacional e internacional que relaciona una mala calidad de alimentación con malnutrición por exceso 33,34,35 y que, las Guías Alimentarias, se alzan como una herramienta educativa eficaz para mejorar o mantener estilos de vida saludables 36 .…”
Section: Resultsunclassified
“…Irrespective of the substantial contributions made by fortified and enriched refined grains ( 3 10 ) to North American diets, such grains are not recommended as foods to increase, with previous and current dietary guidance recommending reduced refined grain consumption in all age groups ( 1 ). An analysis in 7250 participants aged 2–18 y from NHANES 2003–2006 found that without enrichment and fortification practices currently in place in the United States, a substantial percentage of all children and adolescents would have inadequate intakes of numerous micronutrients, with the most concerning nutrient inadequacies affecting older adolescent females ( 11 ).…”
Section: Part 1 Expert Panel Discussion: Can Fortified and Enriched Rmentioning
confidence: 99%
“…Similarly, when assessing refined grain foods in children and adolescents, breads, rolls, tortillas, and RTECs were major contributors of dietary fiber, thiamin, folate, iron, zinc, and niacin to the American diet of children and adolescents. Likewise, breads, rolls, tortillas, and RTECs also provided meaningful amounts of thiamin, niacin, dietary fiber, iron, and folate to older American adults ( 6 10 ). Thus, previous evidence may indicate that classifying all grains that are not whole grains into 1 category of refined grains may not be a fair representation of the nutrient contribution provided by many nutrient-dense enriched grain foods, including breads, rolls, cooked cereals, and RTECs.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, some grain-based foods may contribute greater levels of nutrients to limit, including added saturated fat, added sugar, and sodium. However, in contrast, many grain foods provide positive nutrition to the North American diet and have been shown to be important vehicles of under-consumed nutrients ( 6 9 ). A cluster analyses using data from NHANES 2005–2010 reported that various grain food patterns were positively associated with nutrient intakes and diet quality ( 10 , 11 ), including improved intake of several shortfall nutrients and nutrients of public health concern as identified by the 2015-DGA ( 5 ).…”
Section: Introductionmentioning
confidence: 99%